Answer:
the value of x that makes this equation true is 9
Explanation:
2(x - 6) + x + 14 = 4(x - 3) + 5
open the parenthesis
2x - 12 + x + 14 = 4x - 12 + 5
add 12 to both sides of the equation
2x - 12 + 12 + x + 14 = 4x - 12 + 12 + 5
2x + x + 14 = 4x + 5
subtract 5 from both sides of the equation
2x + x + 14 - 5 = 4x + 5 - 5
3x + 14 - 5 = 4x
3x + 9 = 4x
subtract 3x from both sides of the equation
3x - 3x + 9 = 4x - 3x
9 = 4x - 3x
9 = x
check the answer:
2(x - 6) + x + 14 = 4(x - 3) + 5
2(9 - 6) + 9 + 14 = 4(9 - 3) + 5
29 = 29